Implementation of Corporate Criminal Sanctions Enforcement in Arrears of Bpjs Employment Contributions - Kristiani Asyyere; Habieb Pahlevi; Sanco Simanullang; Yasir Riady (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study aims to analyze the procedures and issues in enforcing criminal sanctions against companies defaulting on BPJS Employment contributions. A normative legal research method was used. The criminal provisions of the BPJS Law are special criminal laws outside the Penal Code and form part of the penal system. The absence of implementing regulations creates a legal vacuum, preventing BPJS Employment from enforcing the mandated penalties. Criminal sanctions targeting corporations lack technical guidelines. Furthermore, BPJS Employment lacks adequate legal authority to report or investigate violations. Key obstacles include conflicts of interest, sectoral ego, and lengthy bureaucracies. Detailed regulations on mechanisms and BPJS Employment's authority to enforce Article 55 of Law No. 24 of 2011 are needed to achieve justice.